AI as a Public Service - Lavista Ferres, Juan M., Elliot K. Fishman, Steven P. Rowe, Linda C. Chu, Elias Lugo-Fagundo (Journal of the American College of Radiology, 2023)
In recent years, artificial intelligence (AI) and machine learning have become increasingly integrated into society. With this shift comes plenty of conflicting information about potential pitfalls and benefits of AI. This information is partial truth and partial hyperbole, which can be confusing as it is hidden in an abundance of jargon. What is AI? The definition of AI has changed over the years, but currently it can be defined as machine learning: algorithms that learn how to generalize from data. In conventional programming humans convert knowledge into rules, but in machine learning the algorithm learns those rules from the data and automatically creates those rules. The power of machine learning is derived from the fact that all we need is data and a success criterion. Machine learning surrounds us with Facebook, YouTube, and Uber, but these same algorithms can be used for much more meaningful endeavors, such …